Deformation Characteristics of Sandy Soil around a Plate Anchor under Lateral Loading - Miao Ren; Tong Jiang; Chen Liu; Junran Zhang; Lijin Wang (Geofluids)
The lateral loading of a plate anchor is a complicated process that involves complex anchor-soil interactions. The deformation characteristics of the soil around an anchor have an important effect on its lateral bearing capacity. In this paper, the noncontact digital image correlation (DIC) technique is used to study the distribution and variation of the soil deformation field under a laterally loaded anchor in sandy soil. The results show that the sand density and embedment ratio significantly affect the distribution and influence range of the active and passive zones around the anchor. The active zone behind the rod gradually decreases with increasing sand density until ultimately disappearing, and the passive zone increases. The maximum influence height occurs in the passive zone behind the rod in dense sand, and the influence range of the passive zone in front of the rod expands with an increasing embedment ratio. Shear bands form during the lateral loading process, which are accompanied by dilatancy in the shear process. The motion path of the rotation center in loose and medium sand is initially rigid translational and then becomes rigid rotational, while the opposite trend occurs in compact dense sand. The results provide important guidance for the development of predictive models for anchor lateral loading and design.